Simulation of high-velocity impact to concrete structures using damage-plasticity model considering large deformation. (15th December 2018) - Eslahi, Reza; Kazemi, Mohammad Taghi
Abstract: In this manuscript, an advanced damage-plasticity model is utilized to simulate response of concrete structures under high-velocity impact. Due to presence of large deformations, it is necessary to incorporate the damage-plasticity model into the finite deformation framework. In high-velocity impact, severe numerical problems could be encountered while updating stress values due to the sudden increase in their levels, especially for the complicated material model used in this study. To overcome these obstacles, an enhancement is made in the nonlinear system of equations of stress- updating procedure. In addition, an adaptive multi-step numerical algorithm is introduced which improves the performance and stability of stress updating. Some computed results of the damage-plasticity model used in this study was compared with existing experimental tests and good agreement was observed. Furthermore, to prove the strength and efficiency of the proposed stress-updating framework, several numerical examples of high-velocity impact to composite steel-concrete structures are provided. It is shown that by using the proposed framework, complicated impact problems could be simulated in a robust and stable fashion.